Pengaruh Penggunaan Materi Pembelajaran Media Aplikasi Instagram @baitul.arabiyah Terhadap Peningkatan Maharah Kalam Santri Pondok Pesantren Ngalah Pasuruan - zahro, fatimatuz; Syarifuddin, Syarifuddin (Lugatuna : Jurnal Prodi PBA, 2023)
Ngalah Pasuruan Islamic Boarding School is one of the many Islamic boarding house in Pasuruan district that has had a Foreign Language Development Program (PPBA) since 2015. This program is located in dormitory I or dormitories for students and there are Arabic, English and Mandarin language programs available. The teaching used grammer-translation method, where learning material is only obtained from students' teaching materials books. This is not very effective in improving language skills, especially in students' speaking skills abilities.The purposes of this study were to find out how and the effect of using learning materials on application media Instagram @baitul.arabiyah on increasing students' speech skill which includes: provision of learning material on Instagram, the ability of students to receive learning material, the ability of students to train their speaking skills with learning material on Instagram that has studied subject matter in the form of (Mufradat) and (Qawaid). The research method used by researchers in this study is a quantitative method. The type of research used was pre-experimental using the one group pre-test post-test design.While the research instruments used for data collection were observation, tests (pre-test and post-test) and documentation. From the results of the study, it was found that the use of learning materials for application media Instagram @baitul.arabiyah with an increase in speaking skills has significance. This is based on the results of hypothesis testing with value 0.000 < 0.05, then the hypothesis is that Ho is rejected and Ha is accepted, it means that there is an influence on the use of learning materials on application media Instagram @baitul.arabiyah on the increase in speaking skills students of PPBA Ngalah Pasuruan Islamic Boarding House